The importance of the navigator nurse in cancer patient care: an integrative literature review (Research, Society and Development, 2022)
Introduction: This article discusses the navigator nurse, its attributions and the main challenges facing this new branch of the profession that is on the rise in the world. The Navigator Nurse is the professional who will provide specific care to the patient from the beginning of treatment, until the end of the patient's life, with a view to monitoring patients throughout the continuum of care, promoting the integration of patients in the health. Methodology: Literature review where the search for articles was carried out between the months of May 2021 to February 2022 in the databases. The descriptors taken from the Descriptors in Health Sciences (DECS) are: “patient navigation”, “oncology nursing” and “nursing care”, combined by the Boolean operator “AND”. Results: After thorough reading and selection, 26 articles were selected. They bring in their contents the care provided by the navigator nurse in the navigation program and its importance in the continuity of care, offering individualized and individual-centered assistance. In addition, they emphasize the benefits of navigation through greater understanding of the disease and treatment, adherence to treatment, positive prognosis and better quality of life. Final Considerations: It was found the importance of patient navigation performed by nurses as a model of care, presenting significant clinical results for cancer patients and their families. The patient navigator should be a professional who partners with patients, serving as an advocate and guide, and prioritizing the patient's needs.